2013
DOI: 10.14712/23361964.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

Does Oeceoclades maculata (Orchidaceae) reabsorb nectar?

Abstract: Nectar is the most common resource offered by orchid flowers. In some cases, flowers reabsorb nectar as part of a resource-recovery strategy. Nectar is present only in the morning in the widespread orchid Oececoclades maculata (Lindl.) Lindl. To determine whether this is due to reabsorption or evaporation of water, the volume of nectar and its concentration in previously bagged flowers were determined throughout the day at two hourly intervals. In addition, the entrance to the nectary of flowers of cultivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…This result hints that the study plant allocates resources to diurnal pollinators (Zimmerman 1988), and this conclusion could potentially be strengthened in future by recording the daily dynamics of the scent production. This is in congruence with a general pattern that pollinators usually visit flowers when the nectar resources are the highest (Real and Rathcke 1991; Aguiar and Pansarin 2013;Biella et al 2019). In addition, our survey indicated that not all flower visitors were long-tongued insects, and not all the pollinators were equal in terms of abundance and visitation behaviour.…”
Section: Discussionsupporting
confidence: 89%
“…This result hints that the study plant allocates resources to diurnal pollinators (Zimmerman 1988), and this conclusion could potentially be strengthened in future by recording the daily dynamics of the scent production. This is in congruence with a general pattern that pollinators usually visit flowers when the nectar resources are the highest (Real and Rathcke 1991; Aguiar and Pansarin 2013;Biella et al 2019). In addition, our survey indicated that not all flower visitors were long-tongued insects, and not all the pollinators were equal in terms of abundance and visitation behaviour.…”
Section: Discussionsupporting
confidence: 89%